Certification of workplaces and risks - Berezutskyi, Viacheslav; Skibniewska, Krystyna; Madieva, Gulmira (ГО "СФБЖДЛ", 2016)
At this material were analyzed of conformity to carry out of certification of workplaces by the old regulatory requirements and international standards that are including the maps of risk a workplaces. New approaches to the procedure for certification of workplaces taking into account the requirements of international standards and risk.

В работе выполнен анализ соответствия, проведенной аттестации рабочих мест по старым нормативным требованиям и международным стандартам, которые предусматривают заполнения карт рисков на рабочие места. Предложены новые подходы в методике проведения аттестации рабочих мест с учетом требований международных стандартов и рисков.
Аттестация рабочих мест и риски
Keywords: certification; workplace; standard; maps of risk; рабочее место; стандарт; нормативные требования; сертификация